Motivation and the impact of transformational leadership on PT. Bintang Sayap Utama Palangka Raya - Arief, Muhammad Laili; Ferdinand, Ferdinand; Darung, Fiasco (JSM: Jurnal Sains Manajemen, 2024)
This research aims to provide empirical explanations regarding the influence of transformational leadership and motivation on the performance of employees at PT. Bintang Sayap Utama in Palangka Raya. The research method employed in this study is quantitative. The population in this research comprises all PT employees. Bintang Sayap Utama in Palangka Raya, totalling 50 individuals, uses a census technique where the entire population is taken as the sample. The collected data were analyzed using multiple linear regression through the SPSS application. The research results indicate that Transformational Leadership (X1) does not have a positive and significant influence on employee performance (Y), whereas motivation (X2) has a positive and significant influence on employee performance (Y). Simultaneously, Transformational Leadership and motivation significantly influence the performance of employees at PT. Bintang Sayap Utama in Palangka Raya